Photoluminescence Kinetics of Dark and Bright Excitons in Atomically Thin MoS2. Issue 10 (21st August 2021) - Eliseyev, Ilya A.; Galimov, Aidar I.; Rakhlin, Maxim. V.; Evropeitsev, Evgenii A.; Toropov, Alexey A.; Davydov, Valery Yu.; Thiele, Sebastian; Pezoldt, Jörg; Shubina, Tatiana V.
Abstract : The fine structure of the exciton spectrum, containing optically allowed (bright) and forbidden (dark) exciton states, determines the radiation efficiency in nanostructures. Time‐resolved microphotoluminescence in MoS2 monolayers (MLs) and bilayers (BLs), both unstrained and compressively strained, in a wide temperature range (10–300 K), is studied to distinguish between exciton states optically allowed and forbidden, both in spin and in momentum, as well as to estimate their characteristic decay times and contributions to the total radiation intensity. The decay times are found to either increase or decrease with increasing temperature, indicating the lowest bright or lowest dark state, respectively. The results unambiguously show that, in an unstrained ML, the spin‐allowed state is the lowest for a series of A excitons (1.9 eV), with the dark state being <2 meV higher, and that the splitting energy can increase several times at compression. In contrast, in the indirect exciton series in BLs (1.5 eV), the spin‐forbidden state is the lowest, being about 3 meV below the bright one. The strong effect of strain on the exciton spectrum can explain the large scatter among the published data and must be taken into account to realize the desired optical properties of 2D MoS2 . Abstract : Time‐resolved microphotoluminescence of atomically thin MoS2 shows that strain can dramatically affect the fine spectrum of exciton states. In unstrained monolayers, the spin‐allowed A exciton is the lowest with dark−bright exciton splitting of <2 meV, whereas compressive strain increases this value by several times. In contrast, the spin‐forbidden state is lowest in the indirect exciton series in bilayers.